Polycystic Ovarian Syndrome (Revista de Medicina Clinica, 2018)
Polycystic ovary syndrome is the most common endocrine disorder in women in reproductive age, and is characterized by the presence of hyperandrogenism with oligo/anovulation. The morphological change in the ovary could be present. In the present article the current classifications are discussed, as well as the physiopathological bases of the disease and its medical and general treatment, especially in relation to the presence of metabolic syndrome as a risk factor for cardio and cerebrovascular events
Keywords: Polycystic ovary sydrome; hiperandrogenism; anovulation; metabolic syndrome